2014
DOI: 10.1186/1471-2202-15-105
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin1/orexinA-immunoreactive axons form few synaptic contacts on rat ventral tegmental area neurons that project to the medial prefrontal cortex

Abstract: BackgroundHypocretins/orexins (Hcrt/Ox) are hypothalamic neuropeptides involved in sleep-wakefulness regulation. Deficiency in Hcrt/Ox neurotransmission results in the sleep disorder narcolepsy, which is characterized by an inability to maintain wakefulness. The Hcrt/Ox neurons are maximally active during wakefulness and project widely to the ventral tegmental area (VTA). A dopamine-containing nucleus projecting extensively to the cerebral cortex, the VTA enhances wakefulness. In the present study, we used ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
(119 reference statements)
1
5
0
Order By: Relevance
“…In both the adult and juvenile participants, narcolepsy patients showed decreased fALFF in bilateral SFGmed, bilateral supra-marginal gyrus and bilateral IPL compared with healthy controls, while narcolepsy patients showed increased fALFF in bilateral SMC and bilateral middle temporal gyrus compared with healthy controls. Both the medial frontal cortex, supra-marginal gyrus, and parietal lobe are abundant in hypocretin projection ( 30 , 31 ), which can explain the reduced fALFF value in these regions among narcolepsy due to hypocretin deficiency, consistent with two previous positron emission tomography studies ( 7 , 8 ). Increased fALFF in bilateral SMC, extending to bilateral paracentral lobule (Figure 1 ), may be a compensation of hypocretin deficiency in motor cortex among narcolepsy, although a contradictory result has been reported hypo-activity in sensorimotor cortex in narcolepsy by transcranial magnetic stimulation (TMS) in a previous study ( 32 ).…”
Section: Discussionsupporting
confidence: 87%
“…In both the adult and juvenile participants, narcolepsy patients showed decreased fALFF in bilateral SFGmed, bilateral supra-marginal gyrus and bilateral IPL compared with healthy controls, while narcolepsy patients showed increased fALFF in bilateral SMC and bilateral middle temporal gyrus compared with healthy controls. Both the medial frontal cortex, supra-marginal gyrus, and parietal lobe are abundant in hypocretin projection ( 30 , 31 ), which can explain the reduced fALFF value in these regions among narcolepsy due to hypocretin deficiency, consistent with two previous positron emission tomography studies ( 7 , 8 ). Increased fALFF in bilateral SMC, extending to bilateral paracentral lobule (Figure 1 ), may be a compensation of hypocretin deficiency in motor cortex among narcolepsy, although a contradictory result has been reported hypo-activity in sensorimotor cortex in narcolepsy by transcranial magnetic stimulation (TMS) in a previous study ( 32 ).…”
Section: Discussionsupporting
confidence: 87%
“…The unique mismatch between the extent of retrograde labelling and the difficulty of identifying and recording mesocortical DA neurons in vivo indicated that this DA subpopulation might either be particularly vulnerable to our labelling protocol or mostly silent under isoflurane anesthesia. The latter possibility is not unlikely given the evidence for orexinergic modulation of mesocortical DA neurons (Del Cid-Pellitero and Garzón, 2014). Furthermore, our study focused on rostral striatal areas not covering the caudal ‘tail’ region, which is a projection area of DA neurons located in the SN pars lateralis.…”
Section: Discussionmentioning
confidence: 99%
“…Orexin released from non-synaptic orexinergic axon varicosities in the dorsal raphe diffused through the extracellular space and activated distant high affinity receptors, providing a longer sustained activation than orexin released through chemical synaptic transmission (Del Cid-Pellitero and Garzón, 2011). Thus, it appears that the excitatory action of orexin in the cerebral cortex might be initiated through two different communication channels.…”
Section: Communication Channels and The Large And Small Orexinergic Bmentioning
confidence: 99%